2005
DOI: 10.1002/pssb.200440024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spin–orbit interaction on the electrical conductivity of three‐dimensional disordered systems

Abstract: A calculation of the effects of spin -orbit interaction on electron transport in 3D disordered systems is presented. We use the Wigner density matrix to construct self-consistent transport equations which can be used to discuss weak localization (quantum interference) effects and even strong localization. The formula for the transport relaxation time has been obtained. The change of the resistivity due to spin-orbit interaction is negative in agreement with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…32 Several research ndings revealed that MR can have negative values as well. 26,33 In disordered systems, spin-orbit interaction plays inuential role in governing the sign of MR. [34][35][36] Interplay between magnetism and electrical properties was explored in BaTiO 3 -SrFe 12 O 19 nanocomposites. 37 Positive and negative MD effect depending on frequency and temperature was observed in these nanocomposites which may be attributed to the induced internal magnetic eld and space charge/interfacial polarization respectively.…”
Section: Introductionmentioning
confidence: 99%
“…32 Several research ndings revealed that MR can have negative values as well. 26,33 In disordered systems, spin-orbit interaction plays inuential role in governing the sign of MR. [34][35][36] Interplay between magnetism and electrical properties was explored in BaTiO 3 -SrFe 12 O 19 nanocomposites. 37 Positive and negative MD effect depending on frequency and temperature was observed in these nanocomposites which may be attributed to the induced internal magnetic eld and space charge/interfacial polarization respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1). We describe the transport properties of the nanostructure in the framework of the two-current model using the spin-dependent Wigner distribution function (WDF) [4]. Taking the z axis along the growth direction and assuming the translational invariance in the lateral directions (x, y), the quantum transport equation for the spin-dependent WDF can be effectively reduced to the one-dimensional form [5]:…”
Section: Model Of Nanodevice and Methods Of Calculationsmentioning
confidence: 99%
“…In order to simulate the electronic transport through the nanostructure, we apply the time-dependent Wigner-Poisson approach, according to which the conduction band electrons are described by the spin-dependent Wigner distribution function. [39][40][41] The quantum kinetic equation takes on the following form 39…”
Section: Theoretical Modelmentioning
confidence: 99%